EVALUATION SUBSTATION PROTECTION SYSTEM FROM LIGHTNING STRIKES AT 150KV JATIGEDE SUBSTATION - Taryo Taryo; Ostadz Al Karim; Jajang Nur Sapaat (Protek: Jurnal Ilmiah Teknik Elektro)
Grounding serves a crucial role in the field lightning protection, electric power, and electric power communications networks. The grounding system's purpose is to guide the flow of electrical charges to the ground mass as rapidly as feasible. The goal of this study is to analyze the grounding system utilized to ensure the continuity of electrical energy production and delivery. In this study, quantitative methods are used to calculate lightning parameters, substation protection by earthing wires and protection towers, earthing system, mesh voltages, touch voltages and step voltages. According to IEEE 80-2013 (latest revision) standards, an ideal earthing application should have a resistance value of 1Ω. The results of the analysis and calculation of the grounding system using the grid grounding type obtained a value of 0.28276 Ω (1Ω), and mesh voltage 0,851314 kV. The protection system which consists of a 103.47288 M ground wire and a 55.27325 M protection tower, is capable of protecting the substation from lightning strikes with a peak current of 51.32913 kA. The touch voltage for humans weighing 50kg and 70kg is 133.39304 V and 180.54060 V, and the step voltage results in 185.5770 V and 251.1690 V. When the grounding current at touch and step voltages is considered, the values become 442.87730 kV and 616.17712 kV. Both exceed the allowed levels of 626 and 2,216 V.